Preputial reconstruction in hypospadias repair. - Castagnetti, Marco; Bagnara, Vincenzo; Rigamonti, Waifro; Cimador, Marcello; Esposito, Ciro (J Pediatr Urol, 2017)
OBJECTIVE: In principle, the prepuce can be reconstructed during hypospadias repair, but the procedure has not gained wide acceptance and preputial reconstruction (PR) is surrounded by several controversies. MATERIAL AND METHODS: A review is provided of the technique for PR, how PR combines with the other steps of hypospadias repair, the risks of complications related to the urethroplasty and specific to PR, and the results of PR with particular regard to the relevance for the patient and his family. RESULTS: PR can be important for patients requiring hypospadias repair and their parents. It can be performed in almost all patients with distal hypospadias except perhaps those with the most asymmetrical prepuces or severe ventral skin deficiency. PR does not seem to increase urethroplasty complications, but combination of PR with tubularisation of the urethral plate urethroplasty seems to offer the best chance of success. Specific complications occur in around 8% of patients and include partial or complete dehiscence of the prepuce and secondary phimosis. To prevent the latter, the reconstructed prepuce should be easily retractile at the end of surgery. Technical modifications can help to achieve this goal. Cosmetically, reconstructed prepuces are not fully normal, but the abnormality could be less important for a patient and his parents that the complete absence of the prepuce. CONCLUSION: On the basis of the evidence summarised above, an algorithm for PR in patients with distal hypospadias is proposed. PR can be offered to the vast majority of distal hypospadias patients, although some modification of the technique for hypospadias repair can be required. Retractility of the reconstructed prepuce at the end of surgery seems paramount for final success.